A retrospective study of enteral nutrition on immune and inflammatory factors after liver cancer surgery. Issue 44 (5th November 2021) - Xu, Yao; Wei, Feng-xiang
Abstract : Abstract: This retrospective study aimed to explore the effect of enteral nutrition (EN) on immune and inflammatory factors after liver cancer surgery (LCS). It was retrospectively conducted on enrolled LCS patients between January 2017 and May 2020. The medical records of 528 patient case records were collected and reviewed. After selection, a total of 80 eligible patient case records were finally included. All those patients received routine diet, and they were allocated to a treatment group (n = 40) and a control group (n = 40). In addition, patients in the treatment group also received EN. The primary outcomes were immune factors (CD4 +, CD8 +, CD4 + /CD8 + ) and inflammatory factors (interleukin-1, interleukin-6, and tumor necrosis factor-α). The secondary outcomes were postoperative hospital stay (day), time to first bowel sounds (hour), time to first flatus (day), time to first defecation (day), and complications. There were not significant differences in CD4 + /CD8 + ( P  = .34), postoperative hospital stay ( P  = .39), and time to first bowel sounds ( P  = .17) between 2 groups. However, there were significant differences in CD4 + ( P  < .01), CD8 + ( P  < .01), interleukin-1 ( P  < .01), interleukin-6 ( P  < .01), tumor necrosis factor-α ( P  < .01), time to first flatus ( P  < .01), and time to first defecation ( P  < .01) between 2 groups. As for complications, there were not significant differences between 2 groups ( P  > .05). The results of this study found that EN may benefit for patients after LCS during the recovery period. Future high quality prospective studies are needed to warrant the present conclusion.